48th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2010
DOI: 10.2514/6.2010-964
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Impedance Characteristics and Power Delivery for Dielectric Barrier Discharge Plasma Actuators

Abstract: Dielectric barrier discharge (DBD) plasma actuators have received recent attention for various flow-control applications. To enable system-level design and optimization of plasma actuator systems-including the actuators and all power electronics-equivalent electrical circuit models of the plasma actuators are desired. To address this need, the current/voltage/power behaviors of different DBD plasma actuators designs are experimentally characterized under sinusoidal electrical excitation at varying amplitudes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
3
7
0
Order By: Relevance
“…The larger capacitance values are consistent with a smaller dielectric thickness. Compared to macroscale DBD devices [9], these microscale devices exhibit smaller resistance and larger capacitance, also consistent with the smaller physical dimensions.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The larger capacitance values are consistent with a smaller dielectric thickness. Compared to macroscale DBD devices [9], these microscale devices exhibit smaller resistance and larger capacitance, also consistent with the smaller physical dimensions.…”
Section: Resultssupporting
confidence: 63%
“…From the voltage and current waveforms, load impedance parameters can be extracted, assuming a simple R-C circuit model to represent the impedance behavior of the plasma. The extraction process follows a previously developed plasma impedance extraction methodology, described in [9]. The resistance is used to model the real power consumed by the device, while the capacitance is used to represent the reactive behavior.…”
Section: Parameter Extractionmentioning
confidence: 99%
“…This operating regime promotes rather a higher resistance power supply than the one proposed for the RL matching network. In addition to the previous case study, Zito et al have also investigated the effect of impedance properties on the power delivery in a DBD plasma actuator and proposed a matching network [34]. In specific, the first part of their research includes the examination of power transfer with respect to the applied voltage and current.…”
Section: Power Supply System Of Plasma Reactorsmentioning
confidence: 99%
“…The actuator is modeled with a resistance and a capacitor of 5 pF in parallel under an applied frequency of 14 kHz. Depending on these parameters, a pair of values for the capacitor and inductor of the matching network has been estimated and ranged between 0 to 1 mF and 25.8 H to 130 nH, respectively [34].…”
Section: Power Supply System Of Plasma Reactorsmentioning
confidence: 99%
“…However, in late 1990s, Roth [3][4][5] popularized a mechanism of generating a directional force by utilizing asymmetrical electrode placement on either side of a dielectric medium. Early results found that indeed these devices induced wall jets along the surface of the dielectric, and extensive work has been carried out in the last decade on characterizing the performance of these actuators with respect to geometry [6][7][8] , electrical parameters [9][10][11] , dielectric properties [11][12][13] , surface chemistry 14 , and underlying physics 15,16 . Thomas et al 17 have written an excellent review of the research done until 2010 on the topic of plasma actuator flow control.…”
Section: Introductionmentioning
confidence: 99%